Pengaruh Metode Role Playing / Bermain Peran Terhadap Aspek Perkembangan Bahasa pada Anak - Kiromi, Ivonne Hafidlatil (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
Game and play has its own meaning and meaning for the child. The game has a meaning as a means of self-socializing (children) means the game is used as a means of bringing children into society, knowing and appreciating the community. Role play is also called symbolic play, pretend, make-believe, imagination. This game is very important for the development of cognition, language, social, and emotion in early childhood. Language is one of the most important things in a child's life, with the child's language being able to interact with others and discover many new things in the environment. With language also, children are able to pour an idea or idea of his wishes. words to express ideas to others Keywords: role playing, language aspect development.